Impact of Axe Bow Hull Shape on Patrol Ship Resistance, Freeboard, and Trim - Suardi, Suardi; Hidayat, Taufik; Firmansyah, Mohammad Bagus; Kyaw, Aung Ye (Maritime Park: Journal of Maritime Technology and Society, 2023)
Patrol Ship is a type of ship that prioritizes speed because of its function to secure water areas. This study uses patrol ship design as the object of study in determining the amount of ship resistance because this ship uses an ax bow hull form, the purpose of this research is to determine the effect of the Axe Bow type hull form on ship resistance, freeboard, and ship trim. The method used in this study is a simulation method with the help of maxsurf software. The results of this study indicate that using the Ax Bow Hull Shape model gives a resistance value of 245.9 kN with a speed of 25 knots, a freeboard value of 0.95, and a trim of 0.006575 m and is included in the "Accepted" category. With these results, the use of the axe bow model for patrol ships can be used as an alternative in selecting the hull shape of a fast ship.